2019
DOI: 10.1371/journal.pgen.1008049
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of BARD1 missense variants in homology-directed repair and damage sensitivity

Abstract: The BARD1 protein, which heterodimerizes with BRCA1, is encoded by a known breast cancer susceptibility gene. While several BARD1 variants have been identified as pathogenic, many more missense variants exist that do not occur frequently enough to assign a clinical risk. In this paper, whole exome sequencing of over 10,000 cancer samples from 33 cancer types identified from somatic mutations and loss of heterozygosity in tumors 76 potentially cancer-associated BARD1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 52 publications
0
30
0
2
Order By: Relevance
“…The BARD1 was the gene that presented more variants associated with HBOC risk. BARD1 form heterodimers with BRCA1 playing an important role as both E3 ubiquitin ligase as homologous repair mediators by recruiting RAD51 to DSB sites [77].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The BARD1 was the gene that presented more variants associated with HBOC risk. BARD1 form heterodimers with BRCA1 playing an important role as both E3 ubiquitin ligase as homologous repair mediators by recruiting RAD51 to DSB sites [77].…”
Section: Discussionmentioning
confidence: 99%
“…Variants in this genes have been associated with a deficiency in HR and increased sensitivity to DNA damage, classifying BARD1 as a gene of moderate penetrance to BC and OC [23,[77][78][79]. All three associated variants are described as VUS on ClinVar, but p.Asn255Ser (c.764A > G) and p.Lys423Arg (c.1268A > G) lack studies characterizing their effects on protein functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four frameshift and 15 nonsense variants in BARD1 have been reported upstream or within BRCT domains, which could result in losing these domains fully or partially and could affect function (Figure 2, Supplementary Table S1). It has been shown that the BARD1 c. 1793C>T; p.Thr598Ile protein isoform exhibits significantly lower homologous recombination DNA repair activity [118]. This isoform might affect binding to PARP1, as the amino acid change is predicted to alter the protein's surface and not any of the known binding sites involved in DNA repair [118].…”
Section: The Biological Impact Of Potentially Pathogenic Variants In mentioning
confidence: 99%
“…It has been shown that the BARD1 c. 1793C>T; p.Thr598Ile protein isoform exhibits significantly lower homologous recombination DNA repair activity [118]. This isoform might affect binding to PARP1, as the amino acid change is predicted to alter the protein's surface and not any of the known binding sites involved in DNA repair [118].…”
Section: The Biological Impact Of Potentially Pathogenic Variants In mentioning
confidence: 99%